A Translation Analysis of the Utilization of Idioms in the Indonesian Subtitles of the Movie Herbie Fully Loaded - Ludfy Pandu Wiranata; Naila Rohmah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the use of idioms and their translation strategies in the Indonesian subtitles of the movie Herbie Fully Loaded. The background of this study stems from the challenges faced in translating non-literal idioms rich in cultural nuances, particularly in audiovisual contexts with technical limitations such as duration and display space. Using a qualitative descriptive approach, this study identified 70 valid idioms that appeared in the movie’s dialogue and visual elements. The idioms were then classified according to Fernando’s (1996) theory into pure idioms, semi-idioms, and literal idioms. The analysis results show that pure idioms and semi-idioms each dominate with a percentage pf 47.14%, while literal idioms only account for 5.72%. Idiom translation strategies were analyzed using Baker’s (2018) theory, and it was found that the most dominant strategy was paraphrasing (85.71%), followed by the use of idioms with similar meanings but different forms (11.43%). Only one idiom was translated using an idiom with similar form and meaning, and one idiom was omitted. The novelty of this study lies in its focus on automotive-themed idioms in family movies, as well as its exploration of te reasons for choosing the paraphrasing strategy in the context of subtitle limitations and cultural differences.